94 Risk factors for lymph node metastasis of ovarian, fallopian tube and primary peritoneal cancer in hereditary breast and ovarian cancer syndrome. (4th December 2020) - Mitamura, Takashi; Sekine, Masayuki; Arai, Masami; Yokoyama, Shiro; Yamashita, Hiroko; Watari, Hidemichi; Yabe, Ichiro; Nomura, Hiroyuki; Enomoto, Takayuki; Nakamura, Seigo
Abstract : Introduction/Background: To establish an individualized surgical strategy for ovarian cancer in patients with the germline BRCA1 and BRCA2 pathogenic variants (BRCA1+ and BRCA2+), we investigated the clinicopathological characteristics that are involved in the increased risk of lymph node metastasis (LNM). Methodology: We retrospectively reviewed the data of 509 Japanese women who underwent BRCA1 and BRCA2 genetic testing and were registered in the database of the Japanese HBOC Consortium. Results: BRCA1+ and BRCA2+ were found in 232 (45.6%) of patients in our database, while other patients had no pathogenic variant (BRCA-). The prevalence of LNM was not markedly different between BRCA- (19.5%), BRCA1+ (18.4%) and BRCA2+ (26.2%). Multivariate analysis revealed an absence of a family history of ovarian cancer as an independent predictor for an increased risk of LNM in BRCA1+, and the prevalence of LNM was 11.7% and 42.0% in the groups with and without a family history of ovarian cancer, respectively. This subgroup without a family history of ovarian cancer did not show any correlation with a particular variant of BRCA1. Conclusion: This study suggested that the existence of a subgroup in which the absence of a family history of ovarian cancer was an independent predictor for an increased risk of lymph node metastasis and certain genetic factors related to the penetrance of hereditary breast and ovarian cancer syndrome might alter the frequency of LNM in BRCA1+ ovarian cancer. We will need to investigate whether or not the same surgical strategy for lymphadenectomy as BRCA- is suitable for this BRCA1+ subgroup. Disclosures: There are no conflict of interest disclosures from any authors.